Legal Protection for Customers in Murabaha Financing Whose Land Ownership Object is Not on Behalf of Sharia Banks to Fulfill Sharia Compliance - Imron, I; Imaniyati, Neni Sri; Firmansyah, Arif (KnE Social Sciences, 2024)
Murabaha financing is one of Sharia banks financing that uses a sale and purchase agreement with a counter-performance in the form of a margin determined in accordance with an agreement between the bank and the customer. The difference between Murabaha contract and credit at a conventional bank is that, in a Murabaha contract, Sharia banks purchase the object (house or land) that the customer wants in advance. Then, the banks sell the house to the customer by informing the amount of the price that has been added with a margin. In practice, not all Sharia banks provide Murabaha financing using this procedure. Therefore, this study aimed to, first, explain the practice of Murabaha financing whose ownership object is not on behalf of Sharia banks in terms of legal protection for customers, and second, find the practice of Murabaha financing whose ownership object is not on behalf of Sharia banks in terms of fulfilling Sharia compliance. The method used is a normative juridical approach with descriptive-analytical research specifications. The data used secondary data, which was collected through library research, and then analyzed by qualitative analysis through legal interpretation methods. The results showed that, first, in terms of legal protection for customers, the practice of this Murabaha financing was not in accordance with internal and external legal protection, and second, in terms of fulfilling Sharia compliance, the practice of this Murabaha financing contained elements of gharar (unclear object) and dzalim (causing injustice). Keywords: protection, customers, financing, Murabaha, Sharia compliance